Формирование межкультурной компетенции у учащихся на основе аутентичных текстов в процессе обучения немецкому языку (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
The article deals with the possibilities of usage original texts and their role in pupils` developing intercultural communicative competence.